Role of Drama Skills in Regulating Students’ Behaviour in Secondary Schools in Central Region, Kenya - Pachomius, Wambugu; Njagi Ndwiga, Zachary; Wachira, Rebecca (International Journal of Academic Research in Progressive Education and Development, 2020)
Discipline among students is very important to their academic performance and, therefore, management of discipline in the learning environment is vital for better learning outcomes. In the recent past, inculcating discipline among students has been the subject of debate among scholars with some suggesting that disciplinary policies simply do not have different effects and that they do not prevent students’ future misbehaviour. As an alternative route to discipline management, involving students in performing arts such as drama activities has been assumed to lead to better disciplinary outcomes. However, this has not been determined in the context of secondary schools in Kenya. The purpose of the study, therefore, was to determine effectiveness of drama skills strategy in regulating students’ behaviour in secondary schools in Central Region, Kenya. The study was guided by Canter’s Assertive Model. The study used descriptive survey design. The target population was 83 deputy principals, 79 drama teachers, and 1888 both drama and non-drama secondary school students in Central Region, Kenya. Stratified sampling was used to get a representative sample size of students. Data was collected from the respondents using questionnaires. Pretesting of instruments was done in schools from Laikipia County. The study used both qualitative and quantitative methods. The quantitative data was analysed using descriptive and inferential statistical techniques with the aid of Statistical Package for Social Scientists (SPSS) and then interpreted and discussed. The study found that the relationship between drama skills regulating and students’ behaviour in secondary schools in Central Region, Kenya was statistically significant. The study therefore recommends that; there is need to encourage and support drama activities in all learning institutions. Finally, school administrators should encourage public speaking through social and academic forums.